2013
DOI: 10.1007/s00232-012-9506-7
|View full text |Cite
|
Sign up to set email alerts
|

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells

Abstract: Pancreatic beta cells act as glucose sensors, in which intracellular ATP ([ATP](i)) are altered with glucose concentration change. The characterization of voltage-gated sodium channels under different [ATP](i) remains unclear. Here, we demonstrated that increasing [ATP](i) within a certain range of concentrations (2-8 mM) significantly enhanced the voltage-gated sodium channel currents, compared with 2 mM cytosolic ATP. This enhancement was attenuated by even high intracellular ATP (12 mM). Furthermore, elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
15
2
Order By: Relevance
“…It was proposed that Na 1 currents may be enhanced by an increase in glucose levels and further ATP production in beta cells (Zou et al, 2013). This idea is supported by whole cell recordings of beta cells in slices from rat pancreas, where concentrations of ATP (2-8 mM) in the recording pipette shift the inactivation curve to more positive potentials and accelerate the recovery from inactivation of VGSC (Zou et al, 2013).…”
Section: Nav Channels Modulation By Endogenous Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that Na 1 currents may be enhanced by an increase in glucose levels and further ATP production in beta cells (Zou et al, 2013). This idea is supported by whole cell recordings of beta cells in slices from rat pancreas, where concentrations of ATP (2-8 mM) in the recording pipette shift the inactivation curve to more positive potentials and accelerate the recovery from inactivation of VGSC (Zou et al, 2013).…”
Section: Nav Channels Modulation By Endogenous Moleculesmentioning
confidence: 99%
“…It was proposed that Na 1 currents may be enhanced by an increase in glucose levels and further ATP production in beta cells (Zou et al, 2013). This idea is supported by whole cell recordings of beta cells in slices from rat pancreas, where concentrations of ATP (2-8 mM) in the recording pipette shift the inactivation curve to more positive potentials and accelerate the recovery from inactivation of VGSC (Zou et al, 2013). In the other direction, the TTXsensitive depolarizing Na 1 influx contributes to the cytosolic Na 1 transients (Nita et al, 2014), which, together with Ca 21 transients, propagate to the mitochondria and modulate ATP synthesis.…”
Section: Nav Channels Modulation By Endogenous Moleculesmentioning
confidence: 99%
“…Pancreatic β-cells act as glucose sensors, where intracellular ATP is altered with glucose concentration change. It has been reported that elevated cytosolic ATP enhanced the activity of Na + channels, which lead to modulation of β-cell excitability and insulin release when blood glucose concentration increases [621]. There also appear to be significant species differences.…”
Section: β-Cellsmentioning
confidence: 99%
“…Although α-and β-cells express the same K ATP channels, the activity is lower in α-cells [24]. In β-cells, Ca 2 + currents dominate electrophysiological activity during exocytosis [25]. In α-cells, although Ca 2 + current is detectable, it only comprises 15 % of the magnitude of the Na + current [26,27].…”
Section: Introductionmentioning
confidence: 99%